LOGO AND PACKAGING CREATION FOR SELLING VALUE DEVELOPMENT FOR BREAD, MSME (LIA BAKERY) IN KEDUNG VILLAGE, GUNUNG KALER, TANGERANG - Bahits, Abdul; Kusuma, Aria Cendana; Fatimah, Andini Nur; Antika, Windi; Dewi, Gita Silviana; Abidzar, Muhammad Daffa (International Journal of Engagement and Empowerment (IJE2), 2024)
This community service activity is aimed at the "Lia Bakery" MSME located in Kedung Village, Gunung Kaler District of Tangerang. The problems faced by this MSME are the lack of understanding in marketing and the lack of selling value, so the business has not developed significantly; thus, this is the main reason for implementing this activity. The assistance in logo and packaging creation for Bread MSME “Lia Bakery" in Kedung Village, Gunung Kaler, Tangerang, aims to increase product competitiveness and added value through more attractive and professional packaging design and brand identity. This program is implemented through several stages, starting from needs analysis and design planning to implementation of the agreed design. A participatory approach is used to work with the business owner to understand product characteristics, target markets, and desired visual preferences. The result of this assistance is the creation of a packaging design that protects the product optimally and has a visual appeal that can increase consumer interest. In addition, the logo design reflects Lia Bakery's unique identity, making it easier for consumers to recognize and remember the product. The impact of this assistance program is expected to increase sales, expand the market, and strengthen the position of the Lia Bakery brand in the local bakery industry